The response of nitrous oxide emissions to different operating conditions in activated sludge wastewater treatment plants in Southeastern Brazil - Ribeiro, Renato P.; Bueno, Rodrigo F.; Piveli, Roque P.; Kligerman, Débora C.; de Mello, William Z.; Oliveira, Jaime L. M. (Water science and technology, 2017)
The continuous measurements of N2O emissions from the aeration tanks of three activated sludge wastewater treatment plants (WWTPs) operated with biological nitrogen removal (BNR) and non-BNR were performed during the different operating conditions of several parameters, such as aeration, dissolved oxygen (DO) profiling and organic shock loading (with landfill leachate). The nitrification process is the main driving force behind N2O emission peaks. There are indications that the variation of the air flow rate influenced N2O emissions; high N2O emissions denote over-aeration conditions or incomplete nitrification, with accumulation of NO2− concentrations. Thus, continuous measurements of N2O emissions can provide information on aeration adequacy and the efficiency of complete nitrification, with major focus on DO control, in order to reduce N2O emissions. An additional concern is the observed propensity of WWTPs in developing countries to receive landfill leachates in their wastewater systems. This practice could have adverse effects on climate change, since wastewater treatment during periods of organic shock loading emitted significantly higher amounts of N2O than without organic shock loading. In short, non-BNR WWTPs are subject to high N2O emissions, in contrast to BNR WWTP with controlled nitrification and denitrification processes.